Cost‐effectiveness of scaling‐up HCV prevention and treatment in the United States for people who inject drugs. (2nd August 2019) - Barbosa, Carolina; Fraser, Hannah; Hoerger, Thomas J.; Leib, Alyssa; Havens, Jennifer R.; Young, April; Kral, Alex; Page, Kimberly; Evans, Jennifer; Zibbell, Jon; Hariri, Susan; Vellozzi, Claudia; et al.
Abstract: Aims: To examine the cost‐effectiveness of hepatitis C virus (HCV) treatment of people who inject drugs (PWID), combined with medication‐assisted treatment (MAT) and syringe‐service programs (SSP), to tackle the increasing HCV epidemic in the United States. Design: HCV transmission and disease progression models with cost‐effectiveness analysis using a health‐care perspective. Setting: Rural Perry County, KY (PC) and urban San Francisco, CA (SF), USA. Compared with PC, SF has a greater proportion of PWID with access to MAT or SSP. HCV treatment of PWID is negligible in both settings. Participants: PWID data were collected between 1998 and 2015 from Social Networks Among Appalachian People, U Find Out, Urban Health Study and National HIV Behavioral Surveillance System studies. Interventions and comparator: Three intervention scenarios modeled: baseline—existing SSP and MAT coverage with HCV screening and treatment with direct‐acting antiviral for ex‐injectors only as per standard of care; intervention 1—scale‐up of SSP and MAT without changes to treatment; and intervention 2—scale‐up as intervention 1 combined with HCV screening and treatment for current PWID. Measurements: Incremental cost‐effectiveness ratios (ICERs) and uncertainty using cost‐effectiveness acceptability curves. Benefits were measured in quality‐adjusted life‐years (QALYs). Findings: For both settings, intervention 2 is preferred to intervention 1 and the appropriate comparator for intervention 2 is the baseline scenario. Relative to baseline, for PC intervention 2 averts 1852 more HCV infections, increases QALYS by 3095, costs 21.6 million more and has an ICER of 6975/QALY. For SF, intervention 2 averts 36 473 more HCV infections, increases QALYs by 7893, costs 872 million more and has an ICER of 11 044/QALY. The cost‐effectiveness of intervention 2 was robust to several sensitivity analysis. Conclusions: Hepatitis C screening and treatment for people who inject drugs, combined with medication‐assisted treatment and syringe‐service programs, is a cost‐effective strategy for reducing hepatitis C burden in the United States.